Narrative structure of Bidayuh animal tales - Florence Gilliam, Kayad; Palisya Siew Ching, Ting (UNIMAS Publisher, 2022)
Chapter 2, by Florence Gilliam Kayad and Palisya Siew-Ching Ting, unravels the uniqueness of Bidayuh folk tales while at the same time affirming the universality of the narrative structure of the tales. Interestingly, tales with animal-human relationship such as “The Tree of Siburan” have more characters and a more complex plot than tales with animal-animal relationship such as “The mouse deer and the snail” and tales with human-animal transformation such as “Sibago, the cockerel”. The authors gauged how familiar some younger Bidayuhs were with the folktales using the reader response approach, and found out that they often only knew the gist of the tales. The authors raised a red flag on the imminent loss of a crucial part of the Bidayuh cultural heritage.